Portfolio Crowding-Out, Empirically Estimated - Frankel, J. A. (Quarterly Journal of Economics, 1985)
This paper tests hypotheses regarding the parameters in investors' asset-demand functions. The hypothesis that federal bonds are closer substitutes for equity than for money implies “portfolio crowding out” by federal borrowing. Regression studies of asset-demand functions have needed to impose prior beliefs to obtain precise and plausible estimates for the parameters. This paper uses a MLE technique that dominates regression in that it makes full use of the constraint that the parameters are not determined arbitrarily but rather are determined by mean-variance optimization on the part of the investor. The striking conclusion is that portfolio effects are close to zero.